Palliative care for those with non-malignant disease: beyond cancer. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Fowell, Andrew; Johnstone, Ros; Cadwalader, Betsi
Abstract : The Integrated Care pathway (ICP) for the last days of life was developed in the 1990's and designed to deliver high quality end of life care in all care settings. The original concept incorporated expected deaths and consequently the tool was applied to cancer patients: the current picture is quite different. The ICP for the last days of life was implemented on an all-Wales basis in 2000 with take-up of the ICP occurring in adult hospices, hospitals, specialist in-patient units and community care settings. The Welsh pathway also has a centralised system for the collection, analysis and feedback of the ICP variances which record instances of goals not being achieved, actions taken and subsequent outcomes. This has resulted in a large database (n=19, 000) reflecting end of life care delivered through the ICP across Wales. The proportion of non-cancer patients receiving end of life care through the ICP has changed notably over the past 10 years. The first 500 ICP variance sheets indicated that 8% of the sample were non-cancer patients, in 2005 the sample (n=607) showed 9% to be non-cancer patients, in 2011 non-cancer patients represent 29% of the sample. Non-cancer patients present with a variety of diagnoses such as renal failure, ischaemic heart disease and COPD. There are no differences between cancer and non-cancer patients on the length of time they are cared for on the ICP or in any aspect of symptom management variance. Conclusion: Although developed with cancer patients in mind the ICP for the last days of life is transferable to other dying patients ensuring that they receive best quality end of life care regardless of diagnosis and care setting.